Strengthening Climate Change Literacy through AI-Based Board Game for Social Studies Teachers and Students in Semarang - Rusdini, Siti Ekowati; Lukitawati, Lukki; Hermanto, Fredy (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
This applied research aims to enhance climate change literacy among Social Studies (IPS) teachers in Semarang City through the development of an AI-based board game. The core issues addressed include low digital literacy, limited access to engaging teaching media, and a lack of inclusive pedagogical approaches. Involving 50 teachers from the MGMP IPS forum, the study adopted a participatory, community-based approach comprising four phases: planning, organizing, implementation, and monitoring and evaluation. Data were collected through interviews, observations, training documentation, and feedback forms. The findings revealed significant improvements in teachers’ digital and pedagogical competencies, along with increased reflective and collaborative learning. The study recommends adopting iterative design methods and ensuring institutional support to sustain this AI-driven instructional innovation in environmental education.